Identification and characterization of iron-related genes in Andean potato cultivars - Hua, X.; Boluarte Medina, T.; Bonierbale, Merideth W.; Williams, M.A.; Veilleux, R.E. (2015)
Andean potato cultivars (Solanum tuberosum Group Andigena) represent a valuable source of genetic diversity of cultivated potato. Unraveling molecular mechanisms effecting iron and zinc accumulation in this gene pool would have tremendous potential to provide a means to help alleviate the prevalence of micronutrient deficiencies in human populations for whom potato is a staple food. By combining data previously obtained from SNP genotyping, QTL mapping and Arabidopsis ferrome orthologs with semi-quantitative RT-PCR analysis, we selected ten candidate genes for analyzing gene expression in response to limited Fe availability using a potato microtuberization system. Four of these genes were up-regulated significantly after iron starvation: MT (Metal Transporter, PGSC0003DMG400024976), Oligopeptide Transporter (PGSC0003DMG400013297), Plasma Membrane H+-ATPase (PGSC0003DMG400033034) and Germin (PGSC0003DMG400018276). Additionally, the function of six metal transporter genes cloned from Andean cv. Señora Warmi (CIP 701243), with comparatively greater Fe and Zn content than other Andean cultivars, was investigated by a yeast complementation assay. Of these genes, IRT1 (Iron Transporter Protein 1, PGSC0003DMG400021155), MT and MTP (Metal Tolerance Protein, PGSC0003DMG400032189) complemented the phenotype of Fe uptake deficient yeast strain, fet3fet4. Likewise, IRT1 and an unannotated IRT homolog complemented Zn uptake in mutant yeast, zrt1zrt2. Expression of MT and MTP genes can also rescue Mn uptake mutant yeast, smf1. These results suggest possible roles of our candidate genes in iron and zinc transport in potato.